A Free-Radical Decarboxylative Coupling of Cinnamic Acids with Acetonitrile - Shang, Xiao-Jie; Chu, Run; Luo, Rui; Zhang, Yanjiang; Liu, Zhong-Quan (Synlett, 2025)
A copper-catalyzed decarboxylative coupling of cinnamic acids with acetonitrile was developed. By using the free-radical hydrogen-atom-transfer strategy to activate the C–H bond in acetonitrile, a series of nitrile compounds were successfully synthesized. This method uses the common solvent acetonitrile as a source of a nitrile group for introduction into organic molecules, avoiding the use of highly toxic nitriles in conventional nitrile compound syntheses.
Keywords: free radicals; C–H bond activation; cinnamic acids; acetonitrile; nitriles; copper catalysis